2008
DOI: 10.1007/s00330-008-1207-3
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting: a single-centre experience with up to 8 years’ follow-up

Abstract: Carotid artery stenting (CAS) may be an alternative to surgical endoarterectomy not only in highrisk patients. We report results in the endovascular treatment of carotid artery disease with up to 8 years' follow-up. In this retrospective study, we analysed data from 853 consecutive patients (946 arteries) treated for carotid artery stenosis between April 1999 and March 2007; 491 (52%) arteries were symptomatic and 455 (48%) were asymptomatic. Preprocedural evaluation of the patients was performed with echo Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…Specific risk factors in the development of restenosis after CAS remains to be elucidated: some studies have identified advanced age [27, 28], hyperglycemia [27, 29], smoke [27] and previous CEA [30]. In our study group, out of all the evaluated clinical radiological and procedural variables, multivariate analysis reveal that the residual stenosis after CAS is a stronger predictor of restenosis with a consistent increased risk of restenosis (1.091 per % unit of residual stenosis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific risk factors in the development of restenosis after CAS remains to be elucidated: some studies have identified advanced age [27, 28], hyperglycemia [27, 29], smoke [27] and previous CEA [30]. In our study group, out of all the evaluated clinical radiological and procedural variables, multivariate analysis reveal that the residual stenosis after CAS is a stronger predictor of restenosis with a consistent increased risk of restenosis (1.091 per % unit of residual stenosis).…”
Section: Discussionmentioning
confidence: 99%
“…The role of diabetes has been described as a predictor of carotid [27, 28] and coronary in-stent restenosis [40] and may be due to smooth muscle cell proliferation common in diabetic patients [41]. The role of neoplasms in the restenosis occurrence is prone to speculative interpretations, in fact a series of cell proliferation regulatory pathways have been associated with plaque progression, stenosis and restenosis after angioplasty as well as in cancer progression [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many trials showed that the risk of ischemic events increases with the degree of stenosis and can be markedly reduced with endarterectomy or carotid artery stenting (CAS) [8, 10, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…It was estimated by the panelists that as many as 80% of patients in the United States undergo carotid endarterectomy after a US examination as the only preoperative imaging study. In our experience more that 1004 CAS, all patients were submitted to CT or MR evaluation pre-stent [23, 26–29]. Therefore, it is of utmost importance that information provided by the US examination be reproducible and reliable [30].…”
Section: Discussionmentioning
confidence: 99%
“…The patients, under light sedation, were kept conscious. The procedure adopted in our institution has been previously described [11]. A single self-expandable stent was implanted to cover the entire lesion in all patients.…”
Section: Methodsmentioning
confidence: 99%